Clinical application of belimumab in lupus nephritis - Zhou Han; Liang Wei; Ding Guo-hua (Linchuang shenzangbing zazhi)
As a human monoclonal antibody specific for B lymphocyte stimulator （BLyS）， belimumab has recently become the first drug approved by the US Food and Drug Administration （FDA） for managing adult active lupus nephritis （LN）. LN affects up to 60% of patients with systemic lupus erythematosus （SLE） and conventional treatment relies largely on hormones and immunosuppressants. However， the proportion of patients with a renal response has remained low. Some LN patients have a 30% risk of developing end-stage renal disease， especially those with type IV LN. Clinical application of belimumab is gaining popularity in LN. This review summarized the latest research advances of belimumab in LN.